ASCVD risk stratification modifies the effect of HbA1c on cardiovascular events among patients with type 2 diabetes mellitus with basic to moderate risk. Issue 1 (9th January 2020) - Zhang, Hongmei; Qin, Li; Sheng, Chang-Sheng; Niu, Yixin; Gu, Hongxia; Lu, Shuai; Yang, Zhen; Tian, Jingyan; Su, Qing
Abstract : Objective: To investigate the association between hemoglobin A1c (HbA1c) 7.0%–8.0% and cardiovascular disease (CVD) risk among Chinese patients with type 2 diabetes mellitus (T2DM) with different baseline 10-year atherosclerotic CVD (ASCVD) risk stratification. Research design and methods: A prospective population-based cohort of 10 060 adults aged 40–70 years in Chongming District of Shanghai was established in 2011. These participants were followed up for 3.25 years and CVD information was recorded. We investigated this association between HbA1c categories and incident CVD stratified by the 10-year ASCVD risk using multiple Cox regression analysis among 1880 patients with T2DM without CVD history. CVD events were defined as cardiovascular death, non-fatal myocardial infarction or non-fatal stroke. Results: The corresponding incidence of CVD per 1000 person-years for the HbA1c≤6.5%, 6.6%–6.9%, 7.0%–8.0% and >8.0% groups were 12.5, 21.8, 22.9 and 28.9, respectively. The HbA1c>8.0% group was significantly associated with a higher CVD risk in patients with T2DM. The HbA1c 7.0%–8.0% group was significantly associated with a higher CVD risk in patients with T2DM with moderate baseline ASCVD risk (HR 2.48; 95% CI 1.15 to 5.32). Conclusion: HbA1c of 7.0%–8.0% may result in a significantly higher CVD risk among patients with T2DM with moderate baseline ASCVD risk, which support the use of HbA1c combined with baseline ASCVD risk assessment to determine future glucose-lowering treatment decisions among patients with T2DM with basic to moderate risk.